Tibor Barna: the redistributive impact of taxes and social policies in the UK: 1937-2005 - Glennerster, Howard (London, 2006)
"Regular annual studies made by the Office of National Statistics in the UK are intended to show how far taxing household incomes and giving benefits in cash and kind to households redistributes income from rich to poor. The first attempt to do this in the UK was made by Tibor Barna for the year 1937. Subsequently his approach has been replicated and elaborated. This study reworks and compares data from various studies to see how the scale and nature of the state’s redistributive role has changed over the past seventy years. Differences in methods and data make comparisons difficult but some broad conclusions can be drawn. Some methodological issues are also discussed on the question of how to approach household equivalisation when services in kind are treated as income."